Elementos impressionistas na obra composicional de Carlos Alberto Pinto Fonseca - Rize Lorentz Matheus (2010)
This thesis aims at demonstrating the presence of elements that are typical of musical impressionism in the work of Carlos Alberto Pinto Fonseca, a composer from Minas Gerais. Based on the works of KOSTKA and PAYNE (1989), COPLEY (1991) and ULEHLA (1994), this research aims at analyzing piano pieces taken from his solo and chamber music repertoire. An attempt is made to expand existing knowledge on the composition legacy of Carlos Alberto Pinto Fonseca, which surpasses the realm of choral singing, of which he was an icon, both as a conductor and as a composer. His musical education as well as other aspects of his compositional work are approached by shedding a new light on interviews given by the composer.